Adipose-derived mesenchymal stem cells (AD-MSCs) in the treatment for psoriasis: results of a single-arm pilot trial - Yao, Danni; Ye, Shuyan; He, Ziyang; Huang, Yu; Deng, Jingwen; Wen, Zehuai; Chen, Xinsheng; Li, Hongyi; Han, Qin; Deng, Hao; Zhao, Robert Chunhua; Lu, Chuanjian (Annals of translational medicine, 2021)
Psoriasis is an immune-mediated inflammatory skin disease that causes significant physical and psychological burden to the patient. While there is currently no curative treatment, recent breakthroughs involving stem cell therapy, in particular, adipose tissue-derived from mesenchymal stem cells (AD-MSCs), have been promising. This single-arm study evaluated the feasibility, safety, and efficacy of AD-MSC infusions for the treatment of moderate to severe psoriasis. A single-center, open-label pilot study was conducted involving seven subjects with moderate to severe psoriasis. Patients received intravenous injections of AD-MSCs (0.5×10 cells/kg) monthly for 12 weeks. The primary outcome was patient safety evaluated by the incidence of adverse events (AEs). Secondary parameters included changes in the Psoriasis Area and Severity Index (PASI), Dermatology Life Quality Index (DLQI), Body Surface Area (BSA), and Pruritus Scores on the Visual Analogue Scale (VAS). A total of 7 patients, including 6 males and 1 female, with an average age of 50.71 years (range, 35-65 years) were enrolled in this study. Four patients completed the trial and two participants completed the one-year follow-up. There were 16 AEs (including 1 grade 2 event and 15 grade 1 events) recorded during the treatment period and 1 serious adverse event (SAE) documented during the follow-up period. The most common AEs were transient fevers (5/16) which were likely to be related to the infusions, followed by pharyngitis (3/16), and headaches (2/16). Both of them were unlikely to be related to the infusions. The procedure was determined to be safe, and no SAEs relating to AD-MSCs were observed. Two patients reached and maintained a PASI-50, indicating a 50% improvement in the PASI score, after one year without any treatment. These results suggested that intravenous injection of AD-MSCs is safe and may be a therapeutic option for the treatment of patients with psoriasis. Future studies involving larger test cohorts and a control group are warranted.